ANALISIS PENGGUNAAN JARINGAN KABEL LISTRIK SEBAGAI MEDIA KOMUNIKASI DATA INTERNET - Imam Suharjo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
The main function of power network is used to deliver electrical energy to meet energy needs. Although this grid has opportunity to use as line transmission that it was only for analog communication and telemetry originally. In the development of research and technology, this network can be used for digital data communications at speeds high enough. In this study conducted a test of feasibility analysis, especially in the use of electricity for the internet data communication. The low voltage electricity network is used in this research. Results from this study, among the tested electrical network on the short distance of less than 400 meters can be used for data communication with the media either. However, if it is used for a more remote distance, the quality will decrease. The real distance depends to the testing equipment and quality of electricity.